"Autonomous Redevelopment": Moving the Masses to Remove Nail Households. (September 2017) - Deng, Yanhua
Autonomous redevelopment is a new approach to demolishing shantytowns in China. It draws on the desire for urban renewal on the part of most residents and encourages dingzihu, or "nail households, " to vacate their property. This is accomplished by formulating rules that link jumpstarting community redevelopment to submission by nail households. Additionally, an ad hoc grassroots organization, the Autonomous Redevelopment Committee (ARC), is often established to facilitate "demolition and relocation" 拆迁. To persuade recalcitrant homeowners, ARC activists rely on emotion work, marginalizing strategies, and collective harassment. Many homeowners, who are initially determined to resist such appeals, ultimately succumb to the power of the masses. Autonomous redevelopment is officially acclaimed as an innovative mass-line approach, relying on a majority of the masses to work on the minority. It suggests a more sophisticated style of authoritarian governance, whereby local authorities use rules, social ties, and grassroots organizations to control popular resistance and to facilitate policy implementation.